Is the future of work childless? Self-employment and fertility - Judite Gonçalves; Pedro S. Martins (Global Labor Organization (GLO), 2019)
The growth of self-employment and in particular gig work may explain part of the declining fertility rates observed in many countries. This study examines this question drawing on longitudinal data to compare women's fertility, proxied by maternity leave uptake, when self-employed or wage workers. It considers the case of Portugal, which allows to focus on structural aspects of work types, as fertility-related social protection there does not discriminate between self-employment and wage work. Results indicate that there are no statistically significant differences in fertility between employees and self-employed women. These findings highlight the importance of social protection for the self-employed, at least as far as their fertility is concerned.
Keywords: C26; J13; J24; 330; fertility; instrumental variables; maternity leave; self-employment